1990
DOI: 10.1002/arch.940150205
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzyme activities in subcellular fractions of larvae of the black swallowtail butterfly, Papilio polyxenes

Abstract: The black swallowtail butterfly, Papilio polyxenes, larvae are specialized feeders of pro‐oxidant rich plants of Apiaceae and Rutaceae. An important defense against toxic forms of oxygen species generated by ingestion of the pro‐oxidants, are the antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT), GSH‐dependent glutathione peroxidases (selenium‐dependent glutathione peroxidase [GPOX] and peroxidase activity of selenium‐independent glutathione‐S‐transferase [GTpx]), and glutathione reductase (GR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Evidence for the dual localization and the existence of SODs with different metal content has also been reported for several lepidopteran species (Ahmad et al, 1988a(Ahmad et al, , 1988b(Ahmad et al, , 1990(Ahmad et al, , 1991.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Evidence for the dual localization and the existence of SODs with different metal content has also been reported for several lepidopteran species (Ahmad et al, 1988a(Ahmad et al, , 1988b(Ahmad et al, , 1990(Ahmad et al, , 1991.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, CAT may have been lost during the centrifugation of the tissue homogenates. However, soluble CAT has been found in mammalian (Masters et al, 1986) as well as insect species (Aucoin et al, 1991;Joanisse and Storey, 1996), and larval homogenates of lepidopteran species have been shown to contain substantial CAT activities in mitochondrial, microsomal and cytosol fractions (Ahmad et al, 1988a(Ahmad et al, , 1988b(Ahmad et al, , 1990. The midgut of honey bee workers contains CAT in peroxisomal as well as soluble fractions (Jimenez and Gilliam, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Ivie et al [35] found that 5% of labeled xanthotoxin still remained in the body of P. polyxenes larvae 24 h after administration of a single dose. Since furanocoumarins produce photodynamically toxic oxygen species such as singlet oxygen and superoxide radicals in the presence of activating wavelengths [2], unmetabolized furanocournarins would be expected to produce toxic oxygen species [17,18]. Ingested harmine, despite its feeding deterrent property, may well be detoxified in P. polyxenes, since harrnine did not affect the nutritional efficiency of the insect.…”
Section: Role Of Antioxidant Enzymes In Detoxification Of Phototoxinsmentioning
confidence: 99%
“…All aerobic organisms possess antioxidant enzymes to detoxify oxyradicals generated from endogenous activities related to respiration and other metabolism [14]. However, in some phytophagous insects, such as P. polyxenes, which are constantly exposed to prooxidants like plant phototoxins during feeding, antioxidant enzymes may be especially important as a detoxification system [15][16][17][18][19]. Increased oxidative stress owing to ingested phototoxins may affect the levels of antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%